Dampak Sektor Pariwisata Terhadap Kesempatan Kerja Di Indonesia (Studi Kasus: Tahun 1980-2011) - Sarwoko Sarwoko (EBBANK, 2013)
The objective of this paper are to examine the long run effects of tourism receipt and national real product domestic brutto on  the employment in Indonesia and the causality relationship among those variables in a multivariate model using annual data spanning 1980-2011. To test the unit root, we employed ADF and PP tests. To test cointegration we used Johansen dan Joselius model (1990) and to test the direction of the causality relationship we used Ngranger causality with VECM or Wald Block Exogeneity test. The empirical findings  show that  the long run equilibrium exists among those variabels and there are unsensitive elasticities between tourism receipt and national real product domestic brutto on  the employment. National real product domestic brutto had had Ngranger causality on  the employment with bidirectional causality, while tourism receipt had had Ngranger causality on employment with unidirectional causality.